2020
DOI: 10.1111/eip.13030
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and metabolic syndrome among clients with first episode psychosis

Abstract: Aim: To explore the relationship between cannabis use and metabolic syndrome (MetS) among those who have experienced first episode psychosis (FEP).Methods: A retrospective analysis of 404 participants enrolled in the Recovery After Initial Schizophrenia Episode-Early Treatment Program (RAISE-ETP) was conducted.Using multiple logistic regression, we investigated the correlation between cannabis use and rate of MetS at baseline and across time as well as the specific metabolic derangements among cannabis users a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Concerning lifestyle, patients consumed more calories and exercised less, and more patients consumed tobacco, cannabis and alcohol on a daily basis than HC subjects. These results are in line with previously published studies and indicate the high prevalence of unhealthy habits in the early stages of psychotic disorders and the necessity of developing specific and intensive programs to improve health habits 24 26 . Some remarkable results of the present study were the changes at the 1-year follow-up in patients with ROP.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Concerning lifestyle, patients consumed more calories and exercised less, and more patients consumed tobacco, cannabis and alcohol on a daily basis than HC subjects. These results are in line with previously published studies and indicate the high prevalence of unhealthy habits in the early stages of psychotic disorders and the necessity of developing specific and intensive programs to improve health habits 24 26 . Some remarkable results of the present study were the changes at the 1-year follow-up in patients with ROP.…”
Section: Discussionsupporting
confidence: 92%
“…In individuals with psychotic disorders, MetS has been associated with genetic variation 7 , 8 , mitochondrial dysfunction 9 12 , antipsychotic treatment 13 16 , clinical severity 6 , 17 , unhealthy lifestyle habits 18 20 and a primary alteration of the innate immune system (imbalance between pro- and anti-inflammatory responses) 21 , 22 . Particularly, patients with FEP show an energy balance exceeding 26% 23 and consumed more saturated fat and exercised less 24 26 . Poor dietary habits have been associated with increased BMI and abdominal obesity 24 and cholesterol levels 26 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of limitations related to the included studies in meta-analysis, two studies (Owiredu et al, 2012;Saloojee et al, 2018) were the only ones conducted on Afro-descendant ethnicity and the overall prevalence increased when those were removed in sensitivity analyses. However, one of them (Saloojee et al, 2018) was the only study that reported cannabis consumption, which has been associated with low odds of MetS in both general population (Vidot et al, 2016) and patients with FEP (Stiles, Alcover, Stiles, Oluwoye, & McDonell, 2020), low odds of overweightness and low odds of non-alcoholic fatty liver in patients with FEP. We were not able to see the influence of cannabis on prevalence accurately.…”
Section: Other Potential Predictors Of Cardiovascular Risks In Fepmentioning
confidence: 99%